Releasing Pattern of Applied Phosphorus and Distribution Change of Phosphorus fractions in the Acid Upland Soils with Successive Resin Extraction - Hartono, Arief (JOURNAL OF TROPICAL SOILS, 2008)
The releasing pattern of applied P  in the acid upland soils and the soil properties influencing the pattern were studied.  Surface horizons of six acid upland soils from Sumatra, Java and Kalimantan were used in this study.  The releasing pattern of applied P (300 mg P kg-1) of these soils were studied by successive resin extraction. P fractionation was conducted to evaluate which fractions released P to the soil solution after successive resin extraction.  The cumulative of resin-Pinorganic (Pi) release of soils was fitted to the first order kinetic. Regression analyses using factor scores obtained from the previous principal components analyses was applied to determine soil properties influencing P releasing pattern. The results suggested that the maximum P release was significantly (P < 0.05) increased by acidity plus 1.4 nm mineral-related factor (PC2) i.e. exchangeable Al and 1.4 nm minerals (smectite and vermiculite) and decreased by oxide related factor (PC1) i.e. aluminum (Al) plus 1/2 iron (Fe) (by ammonium oxalate), crystalline Al and Fe oxides, cation exchange capacity, and clay content.  P fractionation analysis after successive resin extraction showed that both labile and less labile in the form of NaHCO3-Pi and NaOH-Pi fractions, respectively, can be transformed into resin-Pi when in the most labile resin-Pi is depleted.  Most of P released in high oxides soils were from NaOH-Pi fraction while in low oxides soils were from NaHCO3-Pi.  P release from the former fraction resulted in the maximum P release lower than that of the latter one. When NaHCO3-Pi was high, NaOH-Pi was relatively more stable than NaHCO3-Pi despite resin-Pi removal. NaHCO3-Pi and NaOH-Pi are very important P fractions in replenishing resin-Pi in these acid upland soils.